Rediscovery of the myrmecophilous Lucanid genus Xizangia Zhang, 1988 from southwest China (Coleoptera: Scarabaeoidea: Lucanidae) - Huang, Hao; Chen, Chang-Chin (Zootaxa, 2022)
The unexpected rediscovery of the long-lost Penichrolucanini genus Xizangia Zhang, 1988 from China reveals the ant-association of the genus, unlike the termite-association of other Penichrolucanini species from SE Asia. The newly discovered populations of Xizangia from W and S Yunnan belong to a second species of the genus: Xizangia qiuae Huang & Chen, new species. Biological observations are given. Adult morphology including mouthparts, hindwing, male and female genitalia and larval morphology are described in detail for the new species. Brasilucanus alvarengai Vulcano & Pereira, 1961 and Penichrolucanus copricephalus Deyrolle, 1863 are figured in previously undescribed characters of mouthparts, hindwing and female genitalia. The current state of Penichrolucanini systematics is discussed.